Strategi Guru Akidah Akhlak dalam Pembinaan Karakter Toleransi Peserta Didik di Madrasah Ibtidaiyah Negeri 1 Bangka Barat - Indriani, Wiwik (ANWARUL, 2021)
Learning strategy is a system that contains a series of activities specifically to achieve success. This study aims to describe the concept of fostering the character of tolerance of students in Madrasah Ibtidaiyah Negeri 1 West Bangka and to describe the strategy of teachers of moral aqidah in fostering the character of tolerance of students at Madrasah Ibtidaiyah Negeri 1 West Bangka. This study uses a qualitative descriptive method by using literature study analysis, in the process of collecting data, the researcher uses several methods, namely the method of observation, interviews, and documentation. As for the data analysis technique, the researcher used qualitative descriptive analysis techniques. The results of this study indicate that the strategies used by the Akhlaq teacher at Madrasah Ibtidaiyah Negeri 1 Bangka Barat in fostering the tolerance character of students are very diverse and varied, including choosing learning methods that can involve active participation of students, inviting parents to cooperate in helping the implementation of character education, create an effective learning atmosphere, train students to get used to character attitudes and behavior, understand the diverse character of students so that they can apply the right curriculum, the most important thing is that the teacher must be a model or role model for students who can facilitate their duties in carry out character education.